1999
DOI: 10.1007/s11746-999-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of the constituents of susabinori (Porphyra yezoensis)

Abstract: The antioxidant activities of several extracts from Susabinori (Porphyra yezoensis) were measured by the ferric thiocyanate method and the thiobarbituric acid method. The methanol, acetone, ethyl acetate, and hexane extracts, and the chloroform-soluble and water-soluble fractions from the chloroform-methanol extract exhibited higher activities than α-tocopherol. The hot water extract showed little activity. Thinlayer chromatography analysis of the active extracts suggested the existence of several antioxidants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 17 publications
1
45
0
3
Order By: Relevance
“…The antioxidant activities of the MAAs glycine and usujilene have been reported to inhibit lipid peroxidation in aqueous extracts of marine organisms and to scavenge 1 O 2 generated from certain endogenous photosensitizers [147,209]. Yoshiki et al [227] reported a new antioxidant compound from the MAA porphyra-334 by heat treatment.…”
Section: Photoprotective Compounds: Commercial Applicationsmentioning
confidence: 99%
“…The antioxidant activities of the MAAs glycine and usujilene have been reported to inhibit lipid peroxidation in aqueous extracts of marine organisms and to scavenge 1 O 2 generated from certain endogenous photosensitizers [147,209]. Yoshiki et al [227] reported a new antioxidant compound from the MAA porphyra-334 by heat treatment.…”
Section: Photoprotective Compounds: Commercial Applicationsmentioning
confidence: 99%
“…The higher ABTS radical scavenging ability exhibited by the n-hexanic fraction may be explained due to the presence of carotenes/other pigments with long hydrocarbon chain [4] . There are reports which showed that also reported that hexane, chloroform and methanol extracts of Porphyra yezoensis exhibited antioxidant activities [19] attributed to the presence of β-carotene, chlorophyll analogues (pheophytin) and amino compounds (leucine, phenylalanine and mycosporine-like amino acid, usujirene). There are also other reports claiming that seaweeds contain antioxidant compounds which include some pigments such as fucoxanthin and astaxanthin, polyphenols such as phlorotannins, chlorophyll related compounds, phospholipids, flavonoids, bromophenols and polysaccharides [4,15] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we investigated some biological activities related to UV filter requirements including the ethyl derivative 3, which exhibited a higher molar extinction coefficient 21 295 M − 1 .cm −1 . Until now, most mycosporine-like compounds tested for their antioxidant activities are either pure imino-mycosporines or a mixture of several imino-mycosporines [7,[22][23][24][25][26]. Thus, oxo-mycosporines are less reported, and only mycosporine glycine and mycosporine glutaminol glucoside have been tested so far [23,[27][28][29].…”
mentioning
confidence: 99%